Pretreatment-Integration for Milk Protein Removal and Device-Facilitated Immunochromatographic Assay for 17 Items - Zhiwei Qie (Nature Portfolio, 2019)
Abstract Accurate and comprehensive immunochromatographic assay (ICA) data are urgently required in the daily supervision of plants, schools, testing institutions, and law-enforcing departments. Through pretreatment-integration and device-facilitated operation, a quantitative ICA with high sensitivity and throughput was realized on the basis of a commercialized semi-quantitative ICA strip. Three pretreatment methods, namely, acid base, heavy metal salt, and organic solvent methods, have less than three steps. The pretreatment was established for protein removal. A total of 17 pretreated ICA items in milk were considered for the identification of the most suitable pretreatment method. The items are composed of six items pretreated by the acid-base method, six by the heavy salt method, and five by the organic solvent method. Then, the ICA results with pretreatment were compared with those without pretreatment. After pretreatment, the signal intensity increased by 39%, the detection limit decreased to 12%, the half maximal inhibitory concentration decreased to 18%, and the detection range increased fourfold. A device with mixing and centrifugation functions was designed for the pretreatment-related operations. A pre-incubation sampling device was used to facilitate incubation in batch and high-throughput detection. An ICA reader was used. The detection throughput reached 8 samples per batch or 32 samples per hour. The designed devices were printed through 3D printing and rapid prototyping.